Public Banking and Post-Keynesian Economic Theory. Issue 1 (2nd January 2019) - Marshall, Wesley C.; Rochon, Louis-Philippe
Abstract: In this article, we make an appeal for the incorporation of public banking into public discourse regarding the management of the U.S. economy. We argue that the history of post-Keynesian thinking shows a perennial interest in offering solutions to financial and economic problems that often involve the participation of the State. However, in more recent history, discussion has revolved around fiscal and monetary policy, with little consideration given to credit policy and the role of public banking. Basing our arguments on what we believe to be Keynes's most important lessons for the current crisis, we establish several forms in which public banks can confront the economic morass that the Too Big to Fail banks have created.